Comparison Of Pupils’ Completion Rate Before And During 2006/2007 School Feeding Programme In Selected Public Primary Schools In Rivers State, Nigeria - Anero, Nnamdi (Advances in Social Sciences Research Journal, 2020)
The study titled ‘Comparison of pupils’ completion rate before and during 2006/2007 school feeding programme in selected public primary schools in Rivers State, Nigeria was carried out to determine the impact of the feeding programme on the pupils’ completion rate. The study compared the completion rate of pupils before and during the feeding programme and also investigated the completion rate on the bases of boys and girls as well as urban and rural pupils. Out of 868 schools in Rivers State, 44 schools were randomly selected for the study. The Head teachers of the selected schools were requested to supply relevant records of the pupils’ enrolment, dropout, return and completion rates using the admission and attendance registers as well as the result schedules. The figures generated from the records were analyzed using simple percentages. Based on the analysis, the study established that completion rate during the feeding programme was higher than when there was no feeding among pupils in Rivers State. The study further established that there was no significant difference between the completion rates of the urban and rural pupils during or before the feeding programme and also established that more males completed primary education than females during the feeding programme in Rivers State. It therefore recommended that the government should re-introduce the feeding progamme and also carry out enlightenment campaign among the rural dwellers to enable them fully utilize the opportunity as well as seek for participation of philanthropists in funding the programme in all the nooks and crannies of the state so that all and sundry shall benefit.